Weaving a Personal Web: Using online technologies to create customized, connected, and dynamic learning environments - Jessica McElvaney; Zane Berge (The Canadian Network for Innovation in Education (CNIE), 2010)
This paper explores how personal web technologies (PWTs) can be used by learners and the relationship between PWTs and connectivist learning principles. Descriptions and applications of several technologies including social bookmarking tools, personal publishing platforms, and aggregators are also included. With these tools, individuals can create and manage personal learning environments (PLEs) and personal learning networks (PLNs), which have the potential to become powerful resources for academic, professional, and personal development. Résumé : Cet article explore les diverses façons dont les technologies Web personnelles peuvent être utilisées par les apprenants, ainsi que la relation entre ces technologies et les principes d'apprentissage connectivistes. Y sont également présentées les descriptions et les applications de plusieurs technologies, y compris les outils sociaux de mise en signet, les plateformes de publication personnelles et les agrégateurs. Ainsi outillées, les personnes peuvent créer et gérer des environnements d'apprentissage personnels (EAP) et des réseaux d'apprentissage personnels (RAP) qui recèlent le potentiel de devenir de puissantes ressources de perfectionnement sur les plans universitaire, professionnel et personnel.